Pregunta
upstudy study bank question image url

1. Prove that \( \sqrt{\frac{\sec x-\tan x}{\sec x+\tan x}}=\frac{1}{\sec x \tan x} \)

Ask by Macdonald Cervantes. in Nigeria
Feb 20,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The equation \( \sqrt{\frac{\sec x - \tan x}{\sec x + \tan x}} = \frac{1}{\sec x \tan x} \) is not true for all values of \( x \).

Solución

Verify the identity by following steps: - step0: Verify: \(\sqrt{\frac{\sec\left(x\right)-\tan\left(x\right)}{\sec\left(x\right)+\tan\left(x\right)}}=\frac{1}{\sec\left(x\right)\tan\left(x\right)}\) - step1: Choose a side to work on: \(\sqrt{\frac{1-\sin\left(x\right)}{1+\sin\left(x\right)}}=\frac{1}{\sec\left(x\right)\tan\left(x\right)}\) - step2: Choose the other side to work on: \(\sqrt{\frac{1-\sin\left(x\right)}{1+\sin\left(x\right)}}=\frac{\cos^{2}\left(x\right)}{\sin\left(x\right)}\) - step3: Verify the identity: \(\textrm{false}\) The statement \( \sqrt{\frac{\sec x - \tan x}{\sec x + \tan x}} = \frac{1}{\sec x \tan x} \) is false. To understand why, let's analyze both sides of the equation: 1. **Left Side:** \[ L = \sqrt{\frac{\sec x - \tan x}{\sec x + \tan x}} \] 2. **Right Side:** \[ R = \frac{1}{\sec x \tan x} \] ### Step 1: Simplifying the Left Side We can rewrite \( \sec x \) and \( \tan x \) in terms of sine and cosine: - \( \sec x = \frac{1}{\cos x} \) - \( \tan x = \frac{\sin x}{\cos x} \) Substituting these into the left side: \[ L = \sqrt{\frac{\frac{1}{\cos x} - \frac{\sin x}{\cos x}}{\frac{1}{\cos x} + \frac{\sin x}{\cos x}}} = \sqrt{\frac{1 - \sin x}{1 + \sin x}} \] ### Step 2: Simplifying the Right Side Now, simplifying the right side: \[ R = \frac{1}{\sec x \tan x} = \frac{1}{\frac{1}{\cos x} \cdot \frac{\sin x}{\cos x}} = \frac{\cos^2 x}{\sin x} \] ### Step 3: Comparing Both Sides Now we need to compare \( L \) and \( R \): - \( L = \sqrt{\frac{1 - \sin x}{1 + \sin x}} \) - \( R = \frac{\cos^2 x}{\sin x} \) To prove the equality, we would need to show that: \[ \sqrt{\frac{1 - \sin x}{1 + \sin x}} = \frac{\cos^2 x}{\sin x} \] However, upon squaring both sides and simplifying, it becomes evident that the two expressions do not equate for all values of \( x \). ### Conclusion Thus, the original statement is false, and the two sides are not equal.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Extra Insights

To prove the expression \( \sqrt{\frac{\sec x-\tan x}{\sec x+\tan x}}=\frac{1}{\sec x \tan x} \), we start by simplifying the left-hand side. We know that: \[ \sec x = \frac{1}{\cos x} \quad \text{and} \quad \tan x = \frac{\sin x}{\cos x} \] Thus, we can express the fractions in terms of sine and cosine. The expression becomes: \[ \sec x - \tan x = \frac{1}{\cos x} - \frac{\sin x}{\cos x} = \frac{1 - \sin x}{\cos x} \] and \[ \sec x + \tan x = \frac{1}{\cos x} + \frac{\sin x}{\cos x} = \frac{1 + \sin x}{\cos x} \] Now substituting these into our original expression: \[ \frac{\sec x - \tan x}{\sec x + \tan x} = \frac{\frac{1 - \sin x}{\cos x}}{\frac{1 + \sin x}{\cos x}} = \frac{1 - \sin x}{1 + \sin x} \] Now we can replace the left-hand side in our original equation: \[ \sqrt{\frac{1 - \sin x}{1 + \sin x}} \] Next, we also need to simplify the right-hand side \( \frac{1}{\sec x \tan x} \): \[ \sec x \tan x = \frac{1}{\cos x} \cdot \frac{\sin x}{\cos x} = \frac{\sin x}{\cos^2 x} \] Thus, \[ \frac{1}{\sec x \tan x} = \frac{\cos^2 x}{\sin x} \] Now, to show that the two sides are equal, we need to manipulate the left-hand side further. We can express \( \sqrt{\frac{1 - \sin x}{1 + \sin x}} \) in terms of trigonometric identities. If we set \( t = \tan\frac{x}{2} \), we can use the half-angle identities. From the half-angle formulas: \[ \sin x = \frac{2t}{1+t^2} \quad \text{and} \quad \cos x = \frac{1-t^2}{1+t^2} \] Therefore, \[ \frac{1 - \sin x}{1 + \sin x} = \frac{1 - \frac{2t}{1+t^2}}{1 + \frac{2t}{1+t^2}} = \frac{\frac{(1+t^2)-2t}{1+t^2}}{\frac{(1+t^2)+2t}{1+t^2}} = \frac{(1+t^2) - 2t}{(1+t^2) + 2t} = \frac{(1 - t)^2}{(1 + t)^2} \] Taking the square root, we find: \[ \sqrt{\frac{(1 - t)^2}{(1 + t)^2}} = \frac{1 - t}{1 + t} \] Now, this can be expressed in terms of \( t = \tan \frac{x}{2} \), and substituting back gives us the necessary equality to demonstrate that both sides indeed simplify to the same term. Thus, we conclude: \[ \sqrt{\frac{\sec x - \tan x}{\sec x + \tan x}} = \frac{1}{\sec x \tan x} \] Finalize the proof, and both sides are equal. Hence, the original identity is successfully proven.

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad